2003
DOI: 10.1034/j.1600-0404.2003.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic and metabolic disturbances in the acute stage of subarachnoid haemorrhage demonstrated by PET

Abstract: Haemodynamic and metabolic disturbances proved to be common after SAH. These abnormalities probably reflect the primary brain injury caused by the initial haemorrhage. The impact of secondary insults such as acute hydrocephalus, brain oedema, vasospasm, seizures, hypotension and hypoxaemia are likely to be dependent on the degree of primary injury, which can be assessed by PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…However, many such studies have investigated the cerebral circulation and metabolism during delayed CVS, and few have examined the cerebral circulation and metabolism in the early stage before the development of delayed CVS. [5][6][7]11,20,25,26) The cerebral circulation is impaired from the early stages after SAH onwards and CBF is markedly reduced in severe cases. 23) We also confirmed that CBF decreased as the neurological grade increased.…”
Section: Discussionmentioning
confidence: 99%
“…However, many such studies have investigated the cerebral circulation and metabolism during delayed CVS, and few have examined the cerebral circulation and metabolism in the early stage before the development of delayed CVS. [5][6][7]11,20,25,26) The cerebral circulation is impaired from the early stages after SAH onwards and CBF is markedly reduced in severe cases. 23) We also confirmed that CBF decreased as the neurological grade increased.…”
Section: Discussionmentioning
confidence: 99%
“…The data suggest that BOXes stress cells, alter actin architecture, increase LDH release and stimulate respiration by activating ATPases such as myosin ATPase (Butler et al, 1996;Takagi et al, 1989). The occurrence of these events in vivo would contribute to vasospasm/lumenal narrowing, especially if the contractile protein myosin ATPase was stimulated (Butler et al, 1996;Frykholm et al, 2004;Petzold et al, 2003). Bilirubin oxidation products induced changes in contractile proteins in smooth muscle cells might explain that the vessels with chronic vasospasm after SAH are resistant to various types of vasodilatory treatments, so much so that angioplasty is now often used to physically dilate these narrowed vessels (Bejjani et al, 1998;Coyne et al, 1994;Janjua and Mayer, 2003;Zubkov et al, 1999).…”
Section: Boxes Injure Smooth Muscle Cells In Culturementioning
confidence: 97%
“…Their common thread is that higher scores indicate worse clinical condition and result in worse outcomes. SAH results in hemodynamic instability, metabolic disturbances, and neurocardiogenic injury including ventricular dysfunction, cardiac enzyme leak, and electrocardiographic abnormalities (33)(34)(35)(36)(37)(38).…”
Section: Incidence Of Aneurysms and Effects Of Rupturementioning
confidence: 99%